Relationship Between Mathematics Self-Efficacy and Attitudes of Grade 6 Pupils at B. Titong Elementary School - Verano, Remaden (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the relationship between mathematics self-efficacy and attitudes toward mathematics among Grade 6 pupils at B. Titong Elementary School during School Year 2024–2025. Anchored on Social Cognitive Theory, Theory of Planned Behavior, and Expectancy-Value Theory, the study examined mathematics self-efficacy in terms of confidence, persistence, competence, effort, and resilience, and attitudes toward mathematics in terms of interest, enjoyment, anxiety, value, and motivation. A descriptive-correlational research design was used, with total enumeration sampling involving the officially enrolled Grade 6 pupils. Data were gathered through a researcher-made questionnaire validated by experts and analyzed using frequency counts, weighted mean, and Pearson correlation. Findings showed that pupils demonstrated moderate to positive mathematics self-efficacy, particularly in persistence, effort, resilience, competence, and confidence, although lower ratings were noted in independent tasks, formula retention, focus, and confidence after difficult exercises. Pupils also showed generally positive attitudes toward mathematics, with strong recognition of its value, although challenges were observed in word problems, projects, competitions, unfamiliar tasks, and test-related confidence. The Pearson correlation result revealed a statistically significant positive relationship between mathematics self-efficacy and attitudes toward mathematics, with an r-value of 0.64. The major challenges included uncertainty in solving exercises, nervousness, difficulty understanding new topics, discouragement, anxiety, frustration, and lack of motivation. The study concludes that pupils with stronger mathematics self-efficacy tend to demonstrate more favorable attitudes toward mathematics. It supports SDG 4 – Quality Education and SDG 3 – Good Health and Well-Being by promoting learner-centered mathematics instruction and addressing anxiety-related learning concerns. Its sustainability impact lies in strengthening educational, psychosocial, and institutional support systems for more confident, motivated, and resilient learners.